A death by any other name - Arlen, Tessa (Arlen, Tessa. Lady Montfort mystery., 2017)
"A Death by Any Other Name is a delightful Edwardian mystery set in the English countryside. Building on the success of her last two mysteries in the same series, Tessa Arlen returns us to the same universe full of secrets, intrigue, and, this time, roses. The elegant Lady Montfort and her redoubtable housekeeper Mrs. Jackson's services are called upon after a cook is framed and dismissed for poisoning a guest of the Hyde Rose Society. Promising to help her regain her job and her dignity, the pair trek out to the countryside to investigate a murder of concealed passions and secret desires. There, they are to discover a villain of audacious cunning among a group of mild-mannered, amateur rose-breeders. While they investigate, the rumor mill fills with talk about a conflict over in Prussia where someone quite important was shot. There is talk of war and they must race the clock to solve the mystery as the idyllic English summer days count down to the start of WWI. Brimming with intrigue, Tessa Arlen's latest does not disappoint"--